2012
DOI: 10.1371/journal.pone.0035837
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Toll-Like Receptors 2, 4, and 9 Are Highly Associated with Hearing Loss in Survivors of Bacterial Meningitis

Abstract: Genetic variation in innate immune response genes contributes to inter-individual differences in disease manifestation and degree of complications upon infection. We recently described an association of single nucleotide polymorphisms (SNPs) in TLR9 with susceptibility to meningococcal meningitis (MM). In this study, we investigate the association of SNPs in multiple pathogen recognition and immune response genes with clinical features that determine severity and outcome (especially hearing loss) of childhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 49 publications
2
42
1
Order By: Relevance
“…The authors of only three studies have reported an association between TLR9 gene polymorphisms and the development of bacterial meningitis (Sanders et al, 2011;Sanders et al, 2012;van Well et al, 2012). The association between TLR9 gene polymorphisms and susceptibility to meningococcal meningitis was investigated in a study by van Well et al (2012); they found that the TLR9-1237 gene polymorphism increased the risk of hearing loss in patients with bacterial meningitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of only three studies have reported an association between TLR9 gene polymorphisms and the development of bacterial meningitis (Sanders et al, 2011;Sanders et al, 2012;van Well et al, 2012). The association between TLR9 gene polymorphisms and susceptibility to meningococcal meningitis was investigated in a study by van Well et al (2012); they found that the TLR9-1237 gene polymorphism increased the risk of hearing loss in patients with bacterial meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…The association between TLR9 gene polymorphisms and susceptibility to meningococcal meningitis was investigated in a study by van Well et al (2012); they found that the TLR9-1237 gene polymorphism increased the risk of hearing loss in patients with bacterial meningitis. Sanders et al (2012) revealed that the TLR9-1237 gene polymorphism plays a protective role in the development and severity of meningococcal meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TLR2 surface expression itself is up-regulated by NM and its PorB but not by NL and its PorB, providing an additional feedback loop for enhancing cell activation and possibly internalization of invasive strains, but not carriage and commensal strains that express other PorB variants. Lastly, analysis of TLR polymorphisms incidence in humans indicates a potential correlation between TLR signaling and meningococcal pathology, by increased risk of infection and susceptibility to NM with TLR2, TLR4 and TLR9 polymorphisms [48-51]. …”
Section: Discussionmentioning
confidence: 99%
“…bVariations have been reported in Carrasco-Colom et al (2015), Ellis et al (2015), van Well et al (2012) and Yuan et al (2008).…”
Section: Figmentioning
confidence: 99%